Experimental investigations on nanogrinding of RB-SiC wafers. Issue 9 (4th July 2018) - Feng, Guang; Liu, Qiuzu; Guo, Wenliang; Xin, Yupeng; Liang, Qunlong
ABSTRACT: Nanogrinding experiments are performed to investigate the processing characteristics and material removal mechanism of reaction-bonded silicon carbide (RB-SiC) wafers on an ultraprecision grinder using the cup wheel. #120, #600 diamond wheels are used as coarse and semifinished grinding wheels, while #2000 and #12000 diamond wheels are selected as fine and finish grinding wheels, respectively. The experimental results indicate that an ultrasmooth surface with roughness value R a less than 3 nm and groove depth about 5 nm can be achieved using a diamond wheel whose mesh size exceeds 2000. In addition, R a less than 1 nm and groove depth about 2 nm will be obtained with a #12000 diamond wheel. The present study reveals the feasibility of ultraprecision grinding RB-SiC materials in the ductile regime and provides technological insights into nanogrinding of hard materials with an ultrasmooth surface.